Evaluation of torque loss value of MAD/MAM zirconia abutments with prefabricated titanium abutments - Marzieh Alikhasi; Roshanak Baghaie; Nasim khosronejad (Tehran University of Medical Sciences, 2013)
Background and Aims: In response to esthetic demand of patients, ceramic abutments have been developed. Despite esthetic of zirconia abutments, machining accuracy of these abutments has always been a question. Any misfit in the abutment-implant interface connection can lead to detorque and screw loosening. The aim of this study was to compare torque loss value of manually aided design/manually aided manufacture (MAD/MAM) zirconia abutments with prefabricated titanium abutments. Materials and Methods: Seven titanium abutments (Branemark RP, Easy abutment) and seven copy milled abutments which were duplicated from the prefabricated Zirkonzhan (ZirkonZahn, Sand in Taufers, Italy) were prepared. After sintering process of zirconia abutment, all abutments were fastened with a torque screw under 35 Ncm. Detorque measurements were performed per group pushing the reverse button of the Torque controller soon after screw tightening with values registered. The mean torque loss were calculated and compared using Student's t test. Results: The mean of torque loss was 12.71 Ncm with standard deviation of 1.70 for prefabricated titanium abutments and 15.50 Ncm with standard deviation of 4.67 for MAD-MAM abutments. The difference between the two groups was not statistically significant (P=0.23). Conclusion: Within the limitation of this study, MAD-MAM ceramic abutments could maintain the applied torque comparing to the prefabricated abutments.